The influence of liquidity DER ROA and TATO on stock price in wholesale sector and small trade companies on IDX 2017-2021 - Aurelius Tantorio; Purnama Yanti Purba; Catherine Fransisca; Valencia Valencia; Novi Rachma Herawati (Institute of Computer Science (IOCS), 2023)
This study aims to examine and analyze the effect of liquidity, debt to equity ratio, return on assets and total asset turnover on stock prices in large trading and small trading sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. The background of this research is stock prices phenomenon that had decreased in the wholesale and small trade sectors due to decreased company liquidity, decreased return on assets, and decreased total asset turnover. The research method used is descriptive quantitative research which is explanatory research. The data analysis method is multiple linear regressions. The sample of this research is 27 companies with purposive sampling technique. The results of the study state that partially liquidity has no effect and significant effect on stock prices b total asset turnover has no effect and significant effect on stock prices, debt to equity ratio and return on assets have a positive and significant effect on stock prices, and return on assets has a positive effect and significant to stock prices. Simultaneously liquidity, Debt to Equity Ratio, Return on Assets and Total Assets Turnover have a positive and significant effect on stock prices.